PENERAPAN MODEL PEMBELAJARAN TIPE THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR TEMA 2 SUBTEMA 2 SISWA KELAS V SDN KELAPA LIMA KUPANG - Dahlan, Hafifa S.; Koro, Maxsel; Lehan, Andriyani A D (Journal of Character and ELementary Education, 2024)
This research aims to improve student learning outcomes by changing the one-way learning process to two-way learning using the think pair-share learning model. This research uses a classroom action research method which consists of several cycles, each cycle has 4 stages (planning, implementation, observation, and reflection). The data collection strategies used by researchers are observation, tests, and documentation. The research results obtained by researchers were based on research that had been carried out, namely in cycle I using the think pair share type learning model, there were only 9 people (40%) who met the criteria for completion with KKM 75, while 13 students (59%) had not completed it. 90%). In cycle II, 19 students (86%) completed the Think Pair Share type learning model in science learning about types of economic activity in Indonesia. There was an increase in student learning outcomes from cycle I to cycle II, namely by 46%. So in general it is believed that the think pair share type learning model can improve the learning outcomes of class V students in the science and sciences subject regarding types of economic activities in Indonesia.